Análisis Financiero al Sindicato de Choferes Profesionales del cantón Catamayo – provincia de Loja, periodo 2020 – 2021. - Martínez Armijos, Yessica Ariana (2023)
The Curricular Integration Work called Financial Analysis of the Professional Drivers Union of the Catamayo Canton, province of Loja, Period 2020 - 2021, was developed with the purpose of fulfilling the proposed objectives of analyzing the financial-economic situation of the institution. Beginning with the application of the vertical and horizontal analysis to the financial statements, followed by the application of the financial indicators, conclusions and recommendations were established according to the results obtained in the preparation of the report. Regarding the vertical analysis it was established that in the year 2020 it has total assets of $2,097,425.14, while in the year 2021 it reached $2,380,593.73. 593.73, in both years the non-current assets have significant values and the account with the highest representation is property, plant and equipment is the most representative, since, being a purely private organization that provides the service of union association, clinical laboratory (medical center for social assistance), training school for professional drivers and the service station, they have been able to acquire laboratory instruments, spare parts, tools and especially vehicles for its operation and provide a quality and warm service. The land was acquired many years ago, thanks to the first administrations. In the application of the horizontal analysis it was evidenced that the behavior of the groups in the income statement the total income of the year 2020-2021 present an increase of $ 2,879,704.74 that represents 98.88%; where the group of the operational income is the most represented, in the item service station has an increase of $2,256,447.94 with 83.31% for the commercialization of fuel for the benefit of the community and for the hostel Brisa del Valle that operate in joint areas. In addition, the cost of sales increased by 93.62% with a value of $2,136,075.68 for the acquisition of fuel for the organization's service station. In the application of financial indicators, it presents indexes that should be taken into account for decision making and improvements. In the average payment period it allows to know the term that the institution cancels its obligations with suppliers, where in the year 2020 indicates that in 186 days and for the year 2021 is 110 days cancels its accounts pending payment, due to the high volume of purchases in merchandise, showing that the union does not cover satisfactorily with its obligations, so there is no payment policy in which they can emphasize the days established for timely fulfillment of these obligations.